The Effect of FDI, Exports, Inflation on Economic Growth of the America and India 1983–2022 - Rienadi, Novariani Putri; Setyowati, Eni (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to examine the influence of Foreign Direct Investment (FDI), exports, and inflation rates on economic growth in the United States and India. Economic growth is used as an indicator to determine whether a country is classified as a developed or developing country. In 2022, the United States was ranked first as the country with the highest economic growth in the world, reflected in the Gross Domestic Product (GDP) which exceeded USD 25 trillion, while India was ranked fifth with a GDP of USD 3.4 trillion. In the global economy, globalization has brought many positive impacts, one of which is economic openness. This includes international trade without physical barriers and increased foreign investment in various countries. As a result, countries have adjusted their economic policies in response to globalization to encourage economic growth. In addition, external factors have become a focus for countries in managing their economies due to the economic interdependence between countries. By comparing the United States and India, this study seeks to understand the differences in economic growth and policies implemented by these two countries. The Partial Adjustment Model (PAM) approach is used to analyze the United States and India using time series data from 1983 to 2022, which allows understanding the short-term and long-term impact of the independent variables on the dependent variable. The results reveal that in the United States, Foreign Direct Investment and inflation rate significantly affect economic growth, while exports have no effect. In contrast, for India, only Foreign Direct Investment has an impact on economic growth, while exports and inflation rate have no significant effect.